AL-JINĀS FĪ KITĀB TĀRĪKH AL-ADAB AL-‘ARABĪ LIṢ-ṢAFF AS-SĀDIS BI-MA‘HAD DĀR AS-SALĀM KONTŪR: الجناس في كتاب تاريخ الأدب العربي للصف السادس بمعهد دار السلام كونتور - Niza Ni’matul Zahidah; Abdul Hafidz bin Zaid; Riza Nur Laila (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
Balaghah in literary works plays an important role in beautifying a sentence in Arabic. One of the elements in Balaghah is jinas, which is the harmony of sound between two words with different meanings. This research aims to examine the concept of jinas found in the book History of Arabic Literature for 6th grade, which is used as a textbook at the Pondok Modern Darussalam Gontor. The form of this research is literature study, which involves collecting several books related to this title, as well as using a qualitative approach. This research analyzes the science of bahaghah specifically jinas, with a focus on words that contain jinas elements. The method used by the researcher in collecting data is by identifying words that contain jinas, then analyzing them using content analysis techniques. The research result show that the concept of jinas in this book encompasses of jinas in 12 topics. This analysis shows that the use of jinas in this book can enhance the meaning and linguistic appeal of the literary expect presented. Thus, this research contributes to uncovering the aesthetic function and beauty of jinas in literary texts as presented in this book.